2002
DOI: 10.1038/sj.sc.3101276
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of urethral color ultrasound imaging in the diagnosis of female intrinsic sphincter deficiency: preliminary results

Abstract: Study design: Prospective study. Objectives: To evaluate the feasibility of color ultrasound imaging of the urethra in association with UPP to diagnose intrinsic sphincter de®ciency (ISD). Setting: Italy. Methods: We studied a group of 13 normal female volunteers (mean age 29 years) during the estrogenic phase and a group of 15 patients (mean age 63.9 years) with ISD. All patients and normal volunteers underwent color ultrasound imaging using a 4 ± 7 MHz convex broad band transducer. Translabial sagittal scans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Our study was designed to identify a correlation between blood supply and urethral pressure profiles, specifically the MUCP. As found in Siracusano et al's study [23,24] on normal volunteers, our indices were best calculated at the segment closest to the external meatus, where the vascularity was most consistently well seen. Although we were able to reproduce the Doppler waveform RI of the periurethral vasculature, we were not able to correlate RI measurements with either complaints of incontinence or urethral pressure measurements.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our study was designed to identify a correlation between blood supply and urethral pressure profiles, specifically the MUCP. As found in Siracusano et al's study [23,24] on normal volunteers, our indices were best calculated at the segment closest to the external meatus, where the vascularity was most consistently well seen. Although we were able to reproduce the Doppler waveform RI of the periurethral vasculature, we were not able to correlate RI measurements with either complaints of incontinence or urethral pressure measurements.…”
Section: Discussionmentioning
confidence: 59%
“…An additional study done by the same investigator evaluated the resistive index of blood flow surrounding the urethra in healthy young continent patients. This study demonstrated that there is a significantly greater resistive index in the anterior proximal urethra than in the distal and middle urethra [23,24]. Others have hypothesized that normal urethral vascularity contributes up to 30% of the total closure pressure [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, time-consuming and technically difficult to perform for vessels with a small diameter, such as those found in the urethra [4,17,18]. Its use is further limited by the large array of the transducer, by breathing and moving artefacts and by the difficulty in the correct placement of the gate over a small blood vessel, and a false rise in the resistance index (RI) due to pressure on the urethra by the transperineal transducer.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Siracusano et al [36] showed in a small number of women (13 normals and 15 with ISD) that the degree of vascularization along the whole urethra assessed by colour, translabial sagittal ultrasound scans, is different between the two groups and is worth further exploration.…”
Section: Other Measurements Of Intrinsic Sphincter Deficiencymentioning
confidence: 98%